1989
DOI: 10.1172/jci113965
|View full text |Cite
|
Sign up to set email alerts
|

A diabetes-susceptible HLA haplotype is best defined by a combination of HLA-DR and -DQ alleles.

Abstract: HLA-DR4 is associated with insulin-dependent diabetes mellitus (IDDM) in many populations. Many recent studies suggest that the DR4 effect is really due to DQ3.2, an allele of the nearby DQB1 locus. We used T cell clones, MAb, and allelespecific oligonucleotides to test IDDM and control subjects for DR4 subtypes (Dw4, DwlO, Dwl3, and Dw14) and for DR4-associated DQB1 alleles (DQ3.1 and DQ3.2). We find that (a) IDDM is approximately equally associated with alleles of the DRB1 locus (Dw4 and DwlO, combined relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
138
2
6

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(166 citation statements)
references
References 41 publications
20
138
2
6
Order By: Relevance
“…Altogether, the current results integrate well with evidence and speculations pointing to a broad and nonspecific immunopathogenic effect of DR3, 20,30,31 an association of DR3 with islet autoantibody-positivity with or without progression to diabetes, 32 independent associations of DR4 and DQ8 with type 1 diabetes 33 and a delayed effect of DQ that may accelerate or hinder the progression of b-cell destruction and dysfunction. 12,[34][35][36] We previously reported significant clustering and coclustering of islet and celiac autoimmunity in the kindred, explained in part by a common association with DR3-DQ2, which was present in all of 16 relatives with celiac autoimmunity.…”
Section: Differential Effects Of Dr and Dqsupporting
confidence: 85%
“…Altogether, the current results integrate well with evidence and speculations pointing to a broad and nonspecific immunopathogenic effect of DR3, 20,30,31 an association of DR3 with islet autoantibody-positivity with or without progression to diabetes, 32 independent associations of DR4 and DQ8 with type 1 diabetes 33 and a delayed effect of DQ that may accelerate or hinder the progression of b-cell destruction and dysfunction. 12,[34][35][36] We previously reported significant clustering and coclustering of islet and celiac autoimmunity in the kindred, explained in part by a common association with DR3-DQ2, which was present in all of 16 relatives with celiac autoimmunity.…”
Section: Differential Effects Of Dr and Dqsupporting
confidence: 85%
“…53,54 It has been more difficult to ascertain the roles of separate HLA-DR genes. 45,55 Analysis of the linkage between HLA-DQ and DR alleles on DQ8-haplotypes, demonstrated that the frequencies of only certain HLA-DR4-associated DRB1 alleles are increased among T1D patients. 55 This has since been confirmed in larger studies by other groups.…”
Section: Hla-encoded Susceptibility To T1dmentioning
confidence: 99%
“…Similarly, several HLA haplotypes positively associated with Type I diabetes (including DR4-DQB1*0302) were found to encode an amino acid other than aspartate at position 57 of the DQB1 chain, again implying that DQB1 was the primary susceptibility locus [52]. However, an elegant study showed that DR4 haplotypes encoding both DRB*0401 (a subtype of DR4) and DQB*0302 were more diabetogenic than DR4 haplotypes encoding only one of these [53] Âą thus, DRB1 and DQB1 together could confer susceptibility. The HLA-DQA1 locus also appears to be involved in susceptibility [54,55].…”
Section: The Challenges Of Searching For Type I Diabetes Genesmentioning
confidence: 99%